The Use of Compression Sonoelastography in Multiparametric Ultrasound Examination in Cases of Benign Ovarian Formations - Stasiv, Iryna (Journal of Education, Health and Sport, 2021)
Properly diagnosed benign ovarian formations are a condition for appropriate treatment choice. Qualitative assessment of signs detected by multiparametric ultrasound, including compression elastography, is highly effective in the differential diagnosis of benign ovarian formations. Our study became especially relevant for women in the reproductive period since the correct diagnosis influenced the choice of surgical treatment in order to preserve the ovarian reserve. The detailed sonographic aspect of these formations in B-mode, Doppler mode and compression sonoelastography mode is analyzed in the article. Color Flow Mapping, power Doppler and pulsed wave Doppler were used to study blood vessels. Pulsed wave Doppler characterized blood flow quantitatively. Color Flow Mapping was used to determine vessels localization, and power Doppler was used to provide a detailed qualitative assessment of blood flow loci. Elastotype according to the Ueno scale as a qualitative feature and Strain Ratio (coefficient of deformation) as a quantitative indicator were determined for all types of benign ovarian formations. Serous and mucinous cystadenomas were found to belong to elastotypes 0 and I according to the Ueno scale, the papillary component of serous superficial papillomas was mapped as elastotype I and II, fibroids predominantly belonged to elastotype II and III, mature teratoma appertained to elastotypes IV and V. Quantitative coefficient of deformation for all benign ovarian formations ranged from 0.63 to 24.9. According to our results, ultrasound examination of ovarian formations is an accurate and highly informative method for stratification of risks in accordance with the O-RADS classification.